Immediate and Delayed Post Space Preparations in Endodontically Treated Teeth: A Scoping Review - Sadaf Mahmoudi; Pedram Iranmanesh; Saber Khazaei; Maryam Zare Jahromi (BMC, 2022)
Abstract Background The aim of the present review was to identify the effect of the post-space preparation (PSP) timing (immediate or delayed) on endodontically treated teeth. Methods All studies in any language that compared the effect of immediate versus delayed PSP on the outcomes of an endodontically treated tooth were searched in PubMed, Scopus, Web of Science, Cochrane, ProQuest, WorldCat, and Google Scholar databases by two independent researchers until February 12, 2022. Studies assessing merely the immediate or delayed PSP were excluded. A descriptive analysis was performed to evaluate the study design and the characteristics of the included studies. Results The initial search yielded 2612 records, of which 68 were included. Except for one randomized controlled trial, all were in vitro. The evaluated variables were apical/coronal microleakage (n = 48/n = 1), post-bond strength (n = 8), bacterial infiltration (n = 7), presence of voids (n = 3), apical extrusion and residual of filling material (n = 1), and post-operative pain (n = 1). The number of publications had steady growth per year and fast growth per decade. "Post-space preparation" was the most popular keywords. Conclusions The present review highlights the need for further investigations due to the various design of studies, controversial results, and an inadequate number of randomized controlled trials. Trial registration Retrospectively registered. Open Science ( https://doi.org/10.17605/OSF.IO/2YTM6 ).